2020
DOI: 10.1177/0963689720906417
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of a Novel Synthetic Bilirubin Analog as an Antioxidant and Cytoprotective Agent for Pancreatic Islet Transplantation

Abstract: Bilirubin is a natural cytoprotective agent and physiologic doses have proven to be beneficial in various models of organ and cellular transplantation. Recently, we showed that bilirubin has protective effects in models of pancreatic islet transplantation, preventing cell death associated with islet stress and suppressing the release of damage-associated molecular patterns. Despite these promising therapeutic attributes, the natural bilirubin used in these research studies is animal-derived (porcine), making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Interestingly, the digestion of the blank samples without food constituents already showed a certain antioxidant as well as pro-oxidant activity in our study. While there is a lack of research on the pro-oxidant effects of bile and digestive enzymes, several studies have found bile components, such as bilirubin, to have an antioxidant effect due to their ability to bind free radicals, e.g., reactive nitrogen species (RNS) [ 43 , 44 ]. For example, a recent study investigated the in vitro antioxidant effects of two different types of synthetic bilirubin using FRAP and ABTS assays [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the digestion of the blank samples without food constituents already showed a certain antioxidant as well as pro-oxidant activity in our study. While there is a lack of research on the pro-oxidant effects of bile and digestive enzymes, several studies have found bile components, such as bilirubin, to have an antioxidant effect due to their ability to bind free radicals, e.g., reactive nitrogen species (RNS) [ 43 , 44 ]. For example, a recent study investigated the in vitro antioxidant effects of two different types of synthetic bilirubin using FRAP and ABTS assays [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is a lack of research on the pro-oxidant effects of bile and digestive enzymes, several studies have found bile components, such as bilirubin, to have an antioxidant effect due to their ability to bind free radicals, e.g., reactive nitrogen species (RNS) [ 43 , 44 ]. For example, a recent study investigated the in vitro antioxidant effects of two different types of synthetic bilirubin using FRAP and ABTS assays [ 44 ]. The authors reported that both compounds exhibited similar potent antioxidant effects [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GS patient with Covid-19 showed a rapid clinical improvement and short hospital stay as compared with a Covid-19 patient. Indeed, it has been proven that bilirubin exerts potent antioxidant effects which might alleviates Covid-19 induced-oxidative stress ( 9 ). Also, it has been reported that bilirubin has cardioprotective effects, improves endothelial function and provokes the nitric oxide (NO) release ( 10 ), thus, preventing from endothelial dysfunction and cardiovascular complications in COVID-19 ( 11 ), as evident of hypertension in Covid-19 case compared to GS patient with Covid-19.…”
Section: Discussionmentioning
confidence: 99%